(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Anethum sowa L. (Dill) seeds were investigated to determine the fatty acid composition and proximate analyses. The seeds contain 9.36 % fatty oil. The saturated and unsaturated fatty acids contributed 6.22% and 93.78% respectively of the oil. The per cent composition of the extracted oil was identified by Gas Liquid Chromatography (GLC). Among the six fatty acids identified from this study oleic acid contributed the highest proportion (87.10%), where as, linolenic, palmitic, stearic, behenic and arachidic all together contributed the rest (12.90%). Proximate analyses showed that A. sowa. seeds are good source of dietary fibre. Overall Dill seeds oil can be considered as a good source of oleic acid. Key words: Anethum sowa, dill seed oil, fatty acid composition, oleic acid, linolenic acid, Gas liquid chromatography. Bangladesh J. Sci. Ind. Res. 42(4), 455-464, 2007